CSR Commıttees, Gender Dıversıty, And Sustaınabılıty Development Goals Dısclosure - Baiq Zatil Hidayah Fajrina; Eni Indriani (Cita Konsultindo Research Center, 2024)
This study aims to determine the relationship between the existence of a CSR committee and gender diversity in the disclosure of sustainability development goals. The presence of women in the leadership ranks of a company can be one of the drivers of the company being more concerned about the disclosure of sustainability development goals. The samples in this study are companies consecutively listed in the LQ-45 index on the Indonesia Stock Exchange (IDX) for the annual period 2018–2022. The sample selection process in this study used a purposive sampling method. The data analysis used in this research is descriptive statistics, the classical assumption test, and multiple linear regression analysis using SPSS. The results showed that the existence of a CSR committee has no effect on SDGs disclosure, and the presence of women on the board of directors has a positive impact on SDGs disclosure. The only control variables that affect company profitability are the leverage and company size variables, which have no effect.